HUBUNGAN RATA-RATA LAMA SEKOLAH TERHADAP TINGKAT PENGANGGURAN TERBUKA : MEDIASI LAJU PERTUMBUHAN EKONOMI - Muhammad Risal Johar (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2023)
Empirical studies show that the relationship between the average length of schooling and the open unemployment rate is negatively and significantly correlated. Therefore, this study introduces the mediating variable of the rate of economic growth to analyze the path of the relationship between the average length of schooling and the open unemployment rate. The aim of the study was to test whether the rate of economic growth mediates the effect of the average length of schooling on the open unemployment rate. The data used is secondary data in Banten Province in the period 2012-2020. The method used in this research is path analysis. The results of the study indicate that the rate of economic growth mediates the relationship between the average length of schooling and the open unemployment rate by partial mediation. These findings indicate the importance of improving the quality of human resources through length of schooling in order to reduce the open unemployment rate.